Agency as Cosmology: Rethinking Structure, Belief, and Action through Buddhist and Christian Worlds - Yanuardi Syukur (Buletin Antropologi Indonesia, 2026)
This study critically examines Juliana Cassaniti's ethnographic work on Buddhist and Christian communities in Northern Thailand to explore agency cross-culturally. The research objective is to analyze how divergent religious ontologies shape contrasting understandings of human action and challenge universalist models of agency rooted in Western categories. Methodologically, the study employs comparative ethnographic analysis, drawing on Cassaniti's fieldwork alongside theoretical contributions from Archer, Sewell, Ahearn, and Ortner. Results reveal significant contrasts: Christians conceptualize agency as relational and mediated through belief in a divine Other, while Buddhists ground agency in the natural self, governed by karma and personal practice. These findings demonstrate that religious ontologies constitute rather than merely mediate action. The analysis challenges existing frameworks by showing how local epistemologies fundamentally shape agency. The paper raises questions about internal diversity within these traditions and calls for further comparative approaches integrating non-Western frameworks into theoretical discourse. Ultimately, this study contributes to the anthropology of religion by demonstrating the cosmological foundations of human action and enriches understandings of agency as culturally and ontologically situated.